Accumulation of Manganese (Mn) in Tilapia (Oreochromis mossambicus) and Environmental Health Risk Assessment - Mia Azizah; Muhamad Abdul Govin; Nina Ariesta (Journal of Biotropical Research and Nature Technology, 2026)
Situ Tlajung Hilir in Gunung Putri District, Bogor Regency, has been reported to be polluted by industrial waste, which may cause heavy-metal accumulation in tilapia (Oreochromis mossambicus) consumed by the surrounding community. This study aimed to analyze the manganese (Mn) concentration in tilapia and the health risk to people consuming tu sing the Environmental Health Risk Assessment (EHRA) method. Fish samples were collected from three sampling points (A, B, and C) by purposive sampling, while anthropometric and consumption data were obtained through interviews with 30 respondents. Mn concentration was determined using Atomic Absorption Spectrophotometry (AAS) at a wavelength of 279.5 nm following wet digestion. The results showed Mn concentrations of 18.22–18.37 mg/kg (point A), 12.60–12.75 mg/kg (point B), and 6.25–6.29 mg/kg (point C), all exceeding the WHO 2004 standard of 1 mg/kg. The Risk Quotient (RQ) values ranged from 0.0187 (lowest) and 0.0645 (average) to 0.3116 (highest). Because all RQ values were < 1, the community of Situ Tlajung Hilir is still considered safe to consume tilapia under the exposure assumptions applied for up to 30 years ahead; however, these values may change if the rate and frequency of consumption increase.